2019
DOI: 10.1039/c9ra05814a
|View full text |Cite
|
Sign up to set email alerts
|

Development of a near infrared novel bioimaging agent via co-oligomerization of Congo red with aniline and o-phenylenediamine: experimental and theoretical studies

Abstract: With a view to study the effect of insertion of a multifunctional dye moiety on the photo physical properties of conducting polymers, the present paper reports for the first time the homopolymerization and cooligomerization of Congo red (CR) dye with aniline and o-phenylenediamine. The co-oligomerization was established by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy ( 1 H-NMR), and ultraviolet-visible (UV-vis) spectroscopy while the morphology was examined using X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…The UV–visible spectrum of PLu in Figure a revealed peaks at 290 and 420 nm. The 290 nm peak was associated with the π–π* transition, while the 420 nm peak was correlated to the n –π* transition as reported in our previous studies. The same peaks appeared at 300 and 405 nm, respectively, in the theoretically computed spectrum. The experimental UV–visible spectrum of OBB/PLu-20/80 (Figure b) revealed peaks at 350 and 430 nm, whereas the theoretical spectrum revealed peaks at 350 and 450 nm.…”
Section: Results and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The UV–visible spectrum of PLu in Figure a revealed peaks at 290 and 420 nm. The 290 nm peak was associated with the π–π* transition, while the 420 nm peak was correlated to the n –π* transition as reported in our previous studies. The same peaks appeared at 300 and 405 nm, respectively, in the theoretically computed spectrum. The experimental UV–visible spectrum of OBB/PLu-20/80 (Figure b) revealed peaks at 350 and 430 nm, whereas the theoretical spectrum revealed peaks at 350 and 450 nm.…”
Section: Results and Discussionsupporting
confidence: 83%
“…To the best of our knowledge, no work has been reported on the oligomerization of luminol with Bismarck Brown (BB) dye . BB dye has been mostly investigated as a dye pollutant and to date, we do not find any literature based on the utilization of the multi-functionality of BB dye for the design of CPs with enhanced fluorescence characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…On similar grounds, the DFT studies dealing with the reaction of azobenzene with aniline, 1-naphthylamine, luminol and o-phenylenediamine were also attempted using the DFT/B3LYP method with the 6-311G basis set while theoretical 1 H-NMR spectra were obtained by the gauge independent atomic orbital (GIAO) method. 86,87 The theoretically computed spectra matched closely with the experimental findings which confirmed the electronic structure of the synthesized polymers. 88…”
Section: Computational Studies On Miscellaneous Conducting Polymerssupporting
confidence: 74%
“…This conjugation can be further extended if the dye molecule is oligomerized with o -phenylenediamine and is expected to engender novel photo-physical and electronic properties . In our previous studies, we have reported the polymerization of conducting polymers with dyes such as Malachite Green (MG), Congo Red (CR), Sudan Yellow [SY], Azo benzene, Amido Black 10B (AB-10B), Alizarin Red (AR) as well as doping of the conducting polymers with Acid Orange (AO), fluorescein (Fluo), and rhodamine-6G (R6G) dyes . The application of these CPs as imaging agents has also been well-documented. , …”
Section: Introductionmentioning
confidence: 99%